Eksistensi Pembelajaran Al Qur’an Berbasis Ramah ANAK (Studi Kasus Penerapan Program Munaqashah Metode Ummi di TPQ Mafatihul Huda Mantup) - Wahyuni Ahadiyah; Ulil Albab; Denia Venisa Putri (Akademika, 2025)
This thesis discusses the implementation of the Ummi Method Munaqashah Program as a form of children’s domain-based learning of the Qur’an at TPQ Mafatihul Huda Mantup Lamongan using qualitative research and a descriptive approach. The aim of this research is to determine the application of the Ummi method munaqashah program as a form of existence of child-friendly based Al Qur’an learning at TPQ Mafatihul Huda Mantup Lamongan and the supporting and inhibiting factors of implementing the Ummi method munaqashah program as a form of existence of friendly based Al Qur’an learning children at TPQ Mafatihul Huda Mantup Lamongan. To obtain data in this research, researchers used data collection techniques including: observation, interviews, and documentation. Then the analysis technique uses Miles and Huberman’s interactive model including data collection, data condensation, data presentation and drawing conclusions. The results of this research: 1) The implementation of the Ummi method munaqashah program is carried out once a year as a form of the existence of Al Qur’an learning and has brought many changes to the reading of TPQ Mafatihul Huda students for the better, this approach provides a fun and effective approach for students. Students in accordance with child-friendly based learning. The stages of the munaqashah process are: pra munaqashah, munaqashah tartil, munaqashah tahfidz, khotmil qur’an and Imtihan 2) Factors that support this munaqashah program are support from foundations, certified ustadz and ustadzah, the role of parents, guidance and additional time for preparations for munaqashah. The inhibiting factors are a lack of motivation to learn, the influence of gadgets, and children’s abilities that do not meet targets. However, there needs to be a joint effort to improve the quality of learning and support given to students between TPQ, parents and teachers as the most important supporting and inhibiting factors